2020
DOI: 10.1177/2048004020947290
|View full text |Cite
|
Sign up to set email alerts
|

Paravalvular leak closure with real time transesophageal echocardiography and fluoroscopy fusion

Abstract: Transcatheter technology has been increasingly used for paravalvular leak closure. We report the use of “ Fusion Technology” (EchoNaviagator, Phillips, Tustin, CA) that combines real-time 2 and 3 dimensional trans-esophageal echocardiography with fluoroscopy imaging to facilitate paravalvular leak closure. This could help to identify the exact site, size, depth and shape of the paravalvular leak for proper positioning of the occluder device, which may result in saving time and effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Recently, Ahmed et al have named this technology as "Fusion Technique," where they have combined real-time 2D and 3D TEE with fluoroscopy to facilitate closure of PVL. 14 Now that the time of minimally invasive surgery has taken over conventional surgery and fast tracking and enhanced recovery after surgery (ERAS) is the need of the moment, percutaneous PVL closure is preferred over surgical PVL closure. A study done by Gakrinho et al showed that percutaneous PVL closure has a reasonable success rate along with a low complication rate and the results are comparable to surgical treatment in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ahmed et al have named this technology as "Fusion Technique," where they have combined real-time 2D and 3D TEE with fluoroscopy to facilitate closure of PVL. 14 Now that the time of minimally invasive surgery has taken over conventional surgery and fast tracking and enhanced recovery after surgery (ERAS) is the need of the moment, percutaneous PVL closure is preferred over surgical PVL closure. A study done by Gakrinho et al showed that percutaneous PVL closure has a reasonable success rate along with a low complication rate and the results are comparable to surgical treatment in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Em casos de sombras acústicas devido a próteses que apresentam uma limitação significativa ao ETE, o uso do software EchoNavigator, já empregado em procedimentos transcateter de outras valvopatias, pode ser uma ferramenta útil para orientar a equipe intervencionista. 16 A produção de modelos impressos em 3D para o adequado planejamento da intervenção e, também, para treinamento em centros formadores tem emergido como técnica interessante. O primeiro passo é adquirir os dados da imagem em alta qualidade em um formato DICOM (Digital Imaging and Communication in Medicine), seja pela ecocardiografia, tomografia ou outro método.…”
Section: Novos Métodos De Imagem E Situações Especiaisunclassified
“…Real-time CT-fluoroscopy fusion has been attempted in PVL closures, especially in apical surgery [ 105 ]. More recently, EchoNavigator was used to assist interventionalists for treating PVL [ 106 , 107 ]. Ahmed et al particularly noted that EchoNavigator helped identify the exact site, size, depth, and shape of the PVL, and it subsequently facilitated navigating a guidewire across the leak [ 107 ].…”
Section: Current Clinical Applications Of Tee + Fo...mentioning
confidence: 99%
“…More recently, EchoNavigator was used to assist interventionalists for treating PVL [ 106 , 107 ]. Ahmed et al particularly noted that EchoNavigator helped identify the exact site, size, depth, and shape of the PVL, and it subsequently facilitated navigating a guidewire across the leak [ 107 ]. TEE imaging can be useful in PVL cases, as shown in Figure 15 ; however, imaging may be further limited because the presence of the prosthetic valves creates acoustic artifacts (i.e., acoustic shadowing and reverberations).…”
Section: Current Clinical Applications Of Tee + Fo...mentioning
confidence: 99%
See 1 more Smart Citation